2012
DOI: 10.2141/jpsa.011081
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Supplemental DL-2-hydroxy-4-[methylthio] Butanoic Acid and DL-methionine in Diet on Egg Production and Quality in Laying Hens

Abstract: This study was conducted to compare the effects of DL-2-hydroxy-4-[methylthio] butanoic acid (HMB) and DLmethionine (DLM) on egg production performance and egg quality of laying hens. Two hundred and eighty-eight commercial laying hens were assigned to 3 dietary treatment groups and fed the experimental diets from 34 to 46 weeks of age. The bioefficacy of HMB relative to DL-methionine (DLM) was set at 88% (weight/weight), therefore 0.115% of HMB and 0.101% of DLM were added to a basal diet. DLM and HMB supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In Shaoxing laying ducks, the Haugh unit and yolk colour were not affected, but the albumen height and eggshell thickness increased after the Met levels changed from 0·26 to 0·54 % ( 6 ) . Supplementing the diets of laying hens with various formulations of Met had inconsistent effects on the egg quality traits that were affected in the present study with Longyan breeders ( 3 , 20 , 32 ) . In the current study, increasing dietary Met led to linear increases in the albumen weight, together explaining the increase in egg weight and likely accounting for the weight of hatchlings ( 33 ) .…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…In Shaoxing laying ducks, the Haugh unit and yolk colour were not affected, but the albumen height and eggshell thickness increased after the Met levels changed from 0·26 to 0·54 % ( 6 ) . Supplementing the diets of laying hens with various formulations of Met had inconsistent effects on the egg quality traits that were affected in the present study with Longyan breeders ( 3 , 20 , 32 ) . In the current study, increasing dietary Met led to linear increases in the albumen weight, together explaining the increase in egg weight and likely accounting for the weight of hatchlings ( 33 ) .…”
Section: Discussionmentioning
confidence: 54%
“…A similar improvement in egg production was obtained after doubling the amount of Met in the basal diets (0·26 %) of Tsaiya laying ducks for 4 weeks ( 31 ) . Feeding laying hens diets containing 0·26 % Met for 12 weeks starting from 34 weeks of age impaired egg production, egg weight, egg mass and FCR, but adding 0·10 % Met normalised these effects ( 3 ) . In White Leghorn laying hens, Panda et al ( 32 ) showed that egg production, egg weight, egg mass and FCR were not affected by increasing the Met level from 0·30 to 0·42 % in different feed sources for 16 weeks during the peak laying period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methionine is often considered to be the first limiting amino acid for laying hens and supplementation of methionine is important to optimize the performance and health of layers. Considerable evidence in the literature supports the fact that 2hydroxy-4-(methylthio) butanoic acid (HMTBA), and 2-hydroxy-4-(methylthio) butanoic acid-calcium salts (HMTBA-Ca) can replace DL-methionine (DLM) as an effective methionine source in the diet of broilers (Sauer et al 2008), pigs (Kim et al 2006) and laying hens (Liu et al 2005;Bunchasak et al 2012).…”
Section: Introductionmentioning
confidence: 99%